2008
DOI: 10.1167/iovs.08-2009
|View full text |Cite
|
Sign up to set email alerts
|

Disease Course in Patients with Autosomal Recessive Retinitis Pigmentosa due to theUSH2AGene

Abstract: Purpose To estimate the mean rates of ocular function loss in patients with autosomal recessive retinitis pigmentosa due to USH2A mutations. Methods In 125 patients with USH2A mutations, we used longitudinal regression to estimate mean rates of change of Snellen visual acuity, Goldmann visual field area (V4e white test light), and 30 Hz (cone) full-field electroretinogram amplitude. We compared these rates to those of previously studied cohorts with dominant retinitis pigmentosa due to RHO mutations and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
64
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 13 publications
16
64
3
Order By: Relevance
“…This is in line with previous studies on RP patient cohorts, showing a 2% to 3% average annual rate of decline, once BCVA begins to decrease. 33,36,37 The finding that fERG losses precede BCVA decline by many years in USH2 patients is in accordance with a previous study on cone-rod dystrophies where we found that BCVA loss invariably followed fERG loss, with a variable delay of years. 24 We can only speculate as to why fERG is more sensitive than BCVA to central cone deficits.…”
Section: Ferg Decline Compared With Bcva Goldmann Visual Field Declinesupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with previous studies on RP patient cohorts, showing a 2% to 3% average annual rate of decline, once BCVA begins to decrease. 33,36,37 The finding that fERG losses precede BCVA decline by many years in USH2 patients is in accordance with a previous study on cone-rod dystrophies where we found that BCVA loss invariably followed fERG loss, with a variable delay of years. 24 We can only speculate as to why fERG is more sensitive than BCVA to central cone deficits.…”
Section: Ferg Decline Compared With Bcva Goldmann Visual Field Declinesupporting
confidence: 92%
“…[14][15][16]31,36,43 Conversely, fERG decline does not seem to depend on disease onset, but rather it follows an almost stereotyped course with age. It can still be used to estimate the average rate of central cone function decay, 23 but its restricted and almost invariant age window of decline makes it most of all a hallmark of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. Additionally, although retinitis pigmentosa in USH is characterized to have an onset before www.intechopen.com Usher Syndrome: Genes, Proteins, Models, Molecular Mechanisms, and Therapies 299 or during puberty (Smith et al, 1994;Petit, 2001), more and more atypical USH patients have been found (Edwards et al, 1998;Sadeghi et al, 2006;Cohen et al, 2007;Fishman et al, 2007;Sandberg et al, 2008;Malm et al, 2010.;Bashir et al, 2011). These patients have relatively late onset vision loss, which may explain the lack of retinal phenotype in most USH mutant mice, whose lifespan is only about two years.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Type I (USH1) patients have congenital severe to profound deafness as well as vestibular dysfunction; Patients with USH2 exhibit congenital moderate degree of hearing loss and normal vestibular function; and those with USH3 display progressive hearing impairment and occasional vestibular dysfunction. The vision problem of all three types is manifested as retinitis pigmentosa (Hartong et al, 2006;Sadeghi et al, 2006;Fishman et al, 2007;Sandberg et al, 2008;Malm et al, 2011), showing early night and peripheral vision loss and eventual central vision loss.…”
Section: Introductionmentioning
confidence: 99%